2013
DOI: 10.4238/2013.october.30.4
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiling studies on bronchopulmonary dysplasia: a systematic review and meta-analysis

Abstract: ABSTRACT. Over the past several years, several microRNA (miRNA) expression profiling studies have been carried out on bronchopulmonary dysplasia (BPD) in mammalian lung tissues. The most effective way to identify these important miRNAs is to systematically search for similar signatures identified in multiple independent studies. Accordingly, a meta-analysis was conducted to review published miRNA expression profiling studies that compared miRNA expression profiles between BPD lung tissues and normal lung tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Because miRNAs have the ability to modify gene expression rapidly and reversibly, they are ideal mediators for sensing and responding to hypoxic or hyperoxic stress and may therefore be associated with alveolar dysplasias. In a recent analysis by Yang et al 97 , four up-regulated miRNAs (miRNA-21, miRNA-34a, miRNA-431, and Let-7f) and one down-regulated miRNA (miRNA-335) were differentially expressed in BPD lung tissues compared with normal lungs. In addition, eight miRNAs (miRNA-146b, miRNA-29a, miRNA-503, miRNA-411, miRNA-214, miRNA-130b, miRNA-382, and miRNA-181a-1) were found to show differential expression in the process of normal lung development and during the progress of BPD.…”
Section: Biomarkersmentioning
confidence: 96%
“…Because miRNAs have the ability to modify gene expression rapidly and reversibly, they are ideal mediators for sensing and responding to hypoxic or hyperoxic stress and may therefore be associated with alveolar dysplasias. In a recent analysis by Yang et al 97 , four up-regulated miRNAs (miRNA-21, miRNA-34a, miRNA-431, and Let-7f) and one down-regulated miRNA (miRNA-335) were differentially expressed in BPD lung tissues compared with normal lungs. In addition, eight miRNAs (miRNA-146b, miRNA-29a, miRNA-503, miRNA-411, miRNA-214, miRNA-130b, miRNA-382, and miRNA-181a-1) were found to show differential expression in the process of normal lung development and during the progress of BPD.…”
Section: Biomarkersmentioning
confidence: 96%
“…In both mice and human lung tissues, DNA methylation, another form of epigenetic regulation, has been shown to alter expression of genes associated with lung development and alveolar septation including a number of genes in angiogenic pathways [75]. Several studies have also shown that epigenetic regulation by microRNA expression is aberrant in BPD [76, 77]. Transgenic miR-150 knockout mice demonstrate increased angiogenesis when exposed to neonatal hyperoxia that may be due to upregulation of glycoprotein non-metastatic melanoma protein B (GPNMB) [78].…”
Section: Introductionmentioning
confidence: 99%
“…Chorioamnionitis may contribute to fetal lung injury and increase the risk of development of bronchopulmonary dysplasia (BPD), a type of neonatal chronic lung disease (2). Changes in microRNA (miRNA) expression have previously been associated with BPD in mouse and rat models and have also been known to play important roles in inflammation and immune response pathways (3)(4)(5). miRNAs are small noncoding RNAs, 18 to 24 nucleotides in length, that regulate the expression of target genes at the posttranscriptional level by binding to their target mRNAs (6).…”
mentioning
confidence: 99%